2020
DOI: 10.1080/00480169.2020.1778580
|View full text |Cite
|
Sign up to set email alerts
|

Practical oxygen therapy for newborn piglets

Abstract: AIMS: To evaluate the effect of a novel method of practical oxygen therapy on physiological parameters related to survival, weaning weight and preweaning mortality of neonatal piglets under commercial farm conditions. METHODS: Piglets from hyperprolific sows born with signs of asphyxia, (n=109; <6 on a score of respiration, meconium staining and activity) or very low birth weight (VLBW; n=112; <1.05 kg) were selected for the study. Approximately half of each group (n=55 VLBW piglets and n= 57 piglets with asph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This indicates that piglets that had birth assistance might have suffered from a long duration of uterine contractions, which could have led to hypoxia. The piglets that had hypoxia had a lower ability to ingest colostrum than normal piglets [ 30 ]. Supplementation of oxygen immediately after birth in newborn piglets using a specially designed facemask for 45 s to 1 min significantly improved blood oxygen saturation from 86.8% to 97.8% and increased colostrum consumption of piglets from 273.2 to 401.6 g [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that piglets that had birth assistance might have suffered from a long duration of uterine contractions, which could have led to hypoxia. The piglets that had hypoxia had a lower ability to ingest colostrum than normal piglets [ 30 ]. Supplementation of oxygen immediately after birth in newborn piglets using a specially designed facemask for 45 s to 1 min significantly improved blood oxygen saturation from 86.8% to 97.8% and increased colostrum consumption of piglets from 273.2 to 401.6 g [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The piglets that had hypoxia had a lower ability to ingest colostrum than normal piglets [ 30 ]. Supplementation of oxygen immediately after birth in newborn piglets using a specially designed facemask for 45 s to 1 min significantly improved blood oxygen saturation from 86.8% to 97.8% and increased colostrum consumption of piglets from 273.2 to 401.6 g [ 30 ]. This finding indicates that oxygen supplementation can be one practical solution to improve colostrum consumption of the piglets born after manual intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this experiment complement those of earlier studies and highlight the necessity of the development of novel strategies improving the survival and growth of asphyxiated piglets. In this context, the oxygen supply of neonatal piglets is one of the promising strategies reported in the literature; e.g., the recent study of Soraci et al 36 have demonstrated that oxygen supply improved physiological and productive parameters of piglets born with signs of asphyxia or very low birth weight. However the study of Vande Pol et al 37 have revealed that drying of piglets and oxygen supply provided no additional benefit over drying alone, which is contradicting to what reported of Soraci et al 36 and calling for more research.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support the notion that piglets with higher levels of umbilical cord blood lactate have lower birth weights than do piglets with lower levels. This may be due to the fact that small piglets are more likely to experience perinatal hypoxia due to placental insufficiency [ 12 , 48 ]. In addition, piglet vitality is inversely related to this asphyxiation [ 17 , 34 ].…”
Section: Discussionmentioning
confidence: 99%